PERSEPSI MAHASISWA/I UNJ TENTANG TOLERANSI DAN KEBEBASAN DALAM BERAGAMA - Puspa Ayuningrum; Karimah Mutawaqilin Tri Rapani; Lucky Bintang Aprilliano; Lyvia Sastramidjaja; Abdul Fadhil (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
Tolerance is a human attitude or behavior that adheres to the principle of respecting and respecting the behavior of others. In the social, cultural, and religious context, tolerance means attitudes and actions that reject discrimination against different groups or factions in a society. Islam, as a religion that teaches noble teachings, always encourages its people to respect and be tolerant of others, as well as to maintain the purity and truth of its teachings. The facts show that Islam teaches tolerance to all religions. In every situation, Islam as the religion of Rahmatal Lil'alamin always appreciates and respects differences—be it differences in ethnicity, nation, or belief. This shows that Islam provides freedom of speech and tolerance to all religious believers, as well as prioritizing respect for fellow human beings, regardless of existing differences.